Artist to artist 23 major illustrators talk to children about their art. - Carle, Eric (Philomel Books, 2007)
Twenty-three illustrators of children's literature discuss their lives, inspirations, and creative backgrounds and present photographs of themselves and their work spaces along with examples of their illustrations.